Small intestine wall distribution of elastic stiffness measured with 500 MHz scanning acoustic microscopy. - Jørgensen, C; Assentoft, J; Knauss, D; Gregersen, H; Briggs, G (2001)
Obtaining data relating intestinal mechanical properties and histology is a step towards the next level in the hierarchy of structure of living tissue, and may provide new insight into the mechanisms of intestinal function and disease such as obstruction. Due to lack of methodology, however, such data are currently sparse. Scanning acoustic microscopy (SAM) can measure the propagation speed of sound (C) and the acoustic impedance (Z) with micrometer resolution in tissue. By use of elementary theory of elasticity, the elastic stiffness (c11) can be computed from C and Z. We used 5-microm-thick transverse sections of ethanol treated guinea pig small intestine as the experimental model and measured the distribution of C and Z across the intestinal wall using SAM at 500 MHz. The individual layers mucosa, submucosa, and circular and longitudinal muscle were discerned with ease in the images and varied significantly with respect to both C and Z in most cases. The measured values (median values) of C ranged from 1550 to 1669 m s(-1), and Z ranged from 2.10 to 2.60 MPa s m(-1). c11 differed between all layers ranging from 3.25 to 4.27 GPa with the following sequence of magnitude: circular muscle >submucosa>mucosa>longitudinal muscle (p<0.001). In conclusion, we provided the first microscale mechanical data relating to the histological layers of the small intestine.